Cinderella dreams : the allure of the lavish wedding - Otnes, Cele (Life passages., 2003)
A lavish wedding marries two of the most sacred tenets of American culture - romantic love and excessive consumption. This work offers a look at the historical, social and psychological strains that come together to make it the most important cultural ritual in contemporary consumer culture.